Clinical progress and technological innovations in sphincter-preserving treatment for ultra-low rectal cancer - Wu, Fan; Shen, Xiaojun (Frontiers in Oncology, 2026)
Ultra-low rectal cancer (defined as a tumor located within 5 cm from the anal verge) poses unique challenges owing to its distinctive anatomical location, necessitating an optimal balance between oncologic safety and functional preservation. This review focuses on the clinical progress and technological innovations in sphincter-preserving management for ultra-low rectal cancer and is organized within a hierarchical framework encompassing oncologic/anatomical principles, surgical procedures, operative approaches/platforms, specimen-extraction strategies, and multimodal therapy. We first outline plane-based resection principles centered on total mesorectal excision (TME) and key aspects of margin quality control. We then systematically summarize the spectrum of sphincter-preserving procedures, including low/ultra-low anterior resection (LAR/uLAR) and reconstructive options such as coloanal anastomosis (CAA), the transabdominal–transanal approach (TATA), pull-through procedures (Bacon and its modifications), and intersphincteric resection (ISR), with comparisons of indications, oncologic safety, and functional outcomes. Furthermore, we discuss the impact of laparoscopic, robotic, and transanal approaches (e.g., TaTME) on deep pelvic exposure, anatomical precision, and the learning curve, as well as the trade-offs between minimally invasive benefits and safety control associated with specimen-extraction strategies such as NOSE. Finally, we summarize the role of neoadjuvant and total neoadjuvant therapy in facilitating sphincter or organ preservation. Overall, sphincter-preserving treatment for ultra-low rectal cancer should be guided by standardized oncologic principles and tailored combinations of procedures and approaches, with the overarching goal of balancing functional benefit against oncologic safety.